PELAKSANAAN SISTEM MANAJEMEN MUTU (SMM) ISO 9001: 2008 DI SMK NEGERI 2 PENGASIH KULON PROGO TAHUN 2012 - Ipnugraha, Ipnugraha (Faculty of Engineering, Universitas Negeri Yogyakarta, 2012)
ABSTRACTThe purposes of this research are to reveal (1) the implementation of Quality Management System (QMS)of ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo, (2) the factors that support QMSof ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo, and (3) the factors that disturb theimplementation of ISO 9001: 2008 in State Vocational High School 2 of Pengasih Kulon Progo.This study belongs to evaluation research which employed Context model, Input Process, and Product (CIPP).This research was conducted in State Vocational High School 2 of Pengasih Kulon Progo. The data resourceswere the school principal, the representative of Quality Management, the coordinator of School Counseling Guidance, the head of administrative section, library coordinator, and the students. The research instruments werequestionnaire, interview, and documents. Validation technique was by using triangulation, i.e triangulation data,situational data, and data gathering method. Data analysis techniques were qualitative data analysis based onMiles, Huberman dan Spradley, i.e. data analysis with data components which covered data reduction, data display,and conclusion drawing/ verification.The result of the research showed that (1) the implementation of QMS of ISO 9001: 2008 in State VocationalHigh School 2 of Pengasih Kulon Progo had been successful by considering the accomplishment the schoolqualityobjectives. In addition, the implementation of QMS of ISO 9001: 2008 for each component showed ahigh accompolishment, with an average score above 90%, (2) the supporting factors of QMS of ISO 9001: 2008implementation in State Vocational High School 2 of Pengasih Kulon Progo consisted of human resources, RSBIfund, facilities, students high reading interst, provision of the relevant books and magazines for the students, (3)the obstacle factors of QMS of ISO 9001: 2008 implementation in State Vocational High School 2 of PengasihKulon Progo consisted of limited fund, students’ mistake, less publication. Also, the document writing in workingunits were not match with the format of QMS of ISO 9001: 2008, the workload was too high, and there was suddenpersonnel replacement as well as limited area.Keywords: Quality Management System (QMS) of ISO 9001: 2008